Dipyridamole decreases inflammatory metalloproteinase-9 expression and release by human monocytes - Massaro, Marika; Scoditti, Egeria; Carluccio, Maria Annunziata; Pellegrino, Mariangela; Calabriso, Nadia; Storelli, Carlo; Martines, Giuseppe; De Caterina, Raffaele (Thrombosis and Haemostasis, 2013)
Matrix metalloproteinase (MMP)-9 plays an important role in stroke by accelerating matrix degradation, disrupting the blood-brain barrier and increasing infarct size. Dipyridamole is an antiplatelet agent with recognised benefits in ischaemic stroke prevention. In addition to its antiplatelet properties, recent studies have reported that dipyridamole also features anti-inflammatory and anti-oxidant properties. We therefore investigated whether dipyridamole can ameliorate the proinflammatory profile of human monocytes, a source of MMP-9 in stroke, in terms of regulation of MMP-9 activity and expression, and explored underlying mechanisms. Human peripheral blood mononuclear cells (PBMC) and U937 cells were treated with increasing concentrations of dipyridamole (up to 10 µg/ml) for 60 minutes before stimulation with tumour necrosis factor (TNF)-α or phorbol myristate acetate (PMA). Exposure of PBMC and U937 to dipyridamole reduced TNF-α- and PMA-induced MMP-9 activity and protein release as well as MMP-9 mRNA, without significantly affecting the release of TIMP-1. This inhibitory effect was independent of dipyridamole-induced cyclic adeno-sine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP) increase. Correspondingly, dipyridamole also significantly inhibited TNF-α-induced nuclear factor (NF)-κB activation and nuclear translocation of the p65 NF-κB subunit through a mechanism involving the inhibition of IkBα degradation and p38 MAPK activation. In conclusion, dipyridamole, at therapeutically achievable concentrations, reduces the expression and release of MMP-9 through a mechanism involving p38 MAPK and NF-κB inhibition. These results indicate that dipyridamole exerts anti-inflammatory properties in human monocytes that may favourably contribute to its actions in the secondary prevention of stroke, independent of its antiplatelet properties.
Keywords: Dipyridamole; macrophages; matrix metalloproteinase; MMP-9; nuclear factor-κB; p38 MAP kinase; stroke